Association of Hearing Acuity and Cognitive Function Among a Low-Income Elderly Population in Rural China: A Population-Based Cross-Sectional Study - Xu, Yi; Li, Yan; Guo, Dandan; Zhang, Xin; Guo, Huiying; Cao, Hui; Li, Xin; Zhang, Jing; Tu, Jun; Wang, Jinghua; Ning, Xianjia; Yang, Dong (Frontiers in Neuroscience, 2021)
Hearing loss is a modifiable risk factor for dementia and cognitive decline. However, the association between cognition and hearing acuity at different frequencies is unknown. We aimed to assess the relationships between hearing acuity at different frequencies with global cognitive function and five domains of cognition among a low-income elderly population in northern rural China. A population-based cross-sectional study was conducted to collect basic information from elderly residents aged 60 years and older in rural areas of Tianjin, China from April 2012 to November 2013. Pure tone averages at different frequencies in the ear with better hearing and Mini Mental State Examination (MMSE) scores were measured, and the relationships between these variables were assessed. A total of 737 residents aged 60 years or more were enrolled in this study, and the prevalence of hearing impairment was 60.7%. After adjusting for sex, age, education, income, smoking, drinking, systolic blood pressure, total cholesterol, and low-density lipoprotein cholesterol level, MMSE score and immediate recall score were negatively associated with overall pure tone average (OPTA) at four frequencies (0.5, 1, 2, and 4 kHz), pure tone average at low frequencies (LPTA; 0.5, 1, and 2 kHz), and pure tone average at high frequencies (HPTA; 3, 4, and 8 kHz) in the ear with better hearing. Moreover, orientation score was negatively associated with OPTA and LPTA, and the attention and calculation scores were negatively associated with OPTA and HPTA. Each 10-dB increase in OPTA was associated with a MMSE score decrease of 0.464. Each 10-dB increase in LPTA or HPTA was associated with a MMSE score decrease of 0.441 (95% CI: −0.795, −0.086) and 0.351 (95% CI: −0.592, −0.110), respectively. The present study demonstrated significant but weak relationships between OPTA, LPTA, and HPTA with global cognitive function, as defined using MMSE scores; these relationships were independent of age, education, lifestyle factors, and laboratory test values. These results indicated that hearing was associated with cognitive decline among older individuals, who should be screened routinely to identify risk for cognitive decline.